Utilization of diagnostic ultrasound and intravenous lipid-encapsulated perfluorocarbons in non-invasive targeted cardiovascular therapeutics. Issue 1 (December 2016) - Porter, Thomas; Choudhury, Songita; Xie, Feng
Abstract Diagnostic ultrasound (DUS) pressures have the ability to induce inertial cavitation (IC) of systemically administered microbubbles; this bioeffect has many diagnostic and therapeutic implications in cardiovascular care. Diagnostically, commercially available lipid-encapsulated perfluorocarbons (LEP) can be utilized to improve endocardial and vascular border delineation as well as assess myocardial perfusion. Therapeutically, the liquid jets induced by IC can alter endothelial function and dissolve thrombi within the immediate vicinity of the cavitating microbubbles. The cavitating LEP can also result in the localized release of any bound therapeutic substance at the site of insonation. DUS-induced IC has been tested in pre-clinical studies to determine what effect it has on acute vascular and microvascular thrombosis as well as nitric oxide (NO) release. These pre-clinical studies have consistently shown that DUS-induced IC of LEP is effective in restoring coronary vascular and microvascular flow in acute ST segment elevation myocardial infarction (STEMI), with microvascular flow improving even if upstream large vessel flow has not been achieved. The initial clinical trials examining the efficacy of short pulse duration DUS high mechanical index impulses in patients with STEMI are underway, and preliminary studies have suggested that earlier epicardial vessel recanalization can be achieved prior to arriving in the cardiac catheterization laboratory. DUS high mechanical index impulses have also been effective in pre-clinical studies for targeting DNA delivery that has restored islet cell function in type I diabetes and restored vascular flow in the extremities downstream from a peripheral vascular occlusion. Improvements in this technique will come from three dimensional arrays for therapeutic applications, more automated delivery techniques that can be applied in the field, and use of submicron-sized acoustically activated LEP droplets that may better permeate the clot prior to DUS activation and cavitation. This article will focus on these newer developments for DUS therapeutic applications.